Congenital Deficiency of All Vitamin K-Dependent Blood Coagulation Factors Due to a Defective Vitamin K-Dependent Carboxylase in Devon Rex Cats - Soute, Berry A M; Ulrich, Magda M W; Watson, A David J; Maddison, Jill E; Ebberink, Rob H M; Vermeer, Cees (Thrombosis and Haemostasis, 1992)
Two Devon Rex cats from the same litter, which had no evidence of liver disease, malabsorption of vitamin K or chronic ingestion of coumarin derivatives, were found to have plasma deficiencies of factors II, VII, IX and X. Oral treatment with vitamin K1 resulted in the normalization of these coagulation factors. After taking liver biopsies it was demonstrated that the coagulation abnormality was accompanied by a defective γ-glutamyl-carboxylase, which had a decreased affinity for both vitamin K hydroquinone and propeptide. This observation prompted us to study in a well-defined in vitro system the possible allosteric interaction between the propeptide binding site and the vitamin K hydroquinone binding site on carboxylase. It was shown that by the binding of a propeptide-containing substrate to γ-glutamylcarboxylase the apparent KM for vitamin K hydroquinone is decreased about 20-fold. On the basis of these in vitro data the observed defect in the Devon Rex cats can be fully explained.